Endovideoscopic urethra-sparing simple prostatectomy via an extraperitoneal approach as treatment of benign prostatic hyperplasia - Stanislav N. Volkov; Vitaliy I. Tereshchenko; Vladimir S. Stepanchenko; Robert K. Mikheev; Olga R. Grigoryan; Elena N. Andreeva; Konstantin B. Kolontarev (ZAO "Consilium Medicum", 2023)
Aim. To evaluate the efficacy of endovideoscopic urethra-sparing simple prostatectomy via an extraperitoneal approach (EUSP) for patients with benign prostatic hyperplasia. Materials and methods. In the period from January 2021 until September 2022 8 patients underwent EUSP. Initial clinical datas, perioperative and postoperative outcomes, implications, IPSS questionnaires, IIEF-5 and ejaculatory datas have been evaluated. The technique of the present method was adopted from Ping Wang, Dan Xia, SunYi Ye, DeBo Kong, Jie Qin, TaiLe Jing, YeQing Mao, HongZhou Meng, Shuo Wang (2018). Results. Seven (87.5%) patients underwent EUSP successfully, 1 (12.5%) patient needed conversion into open simple prostatectomy. Mean time of operation was 171 minutes (150-185), mean blood loss was 232 ml (180-300). In 2 (25%) cases urethral reconstruction after damage was needed. Mean catheterization time was 1.5 days (1-4). According to Clavien-Dindo classification (2004) such complications were found: low degree - 2 (1 or 2 group), 3а group - 1 (severe hematuria, when bladder infusion is needed). Mean management time was 8.4 months (6-11). Results from post-operative questionnaire IPSS (p0.1) и QoL (p0.1) significantly improved. Totally 4 patients had secure erectile function: 3 of them had normal erection, the last one (1) - retrograde ejaculation. Conclusion. EUSP is technically applicable for patients with benign prostatic hyperplasia. Patients have shorter time of catheterization, risk profile, significant improvement of urination и support of antegrade ejaculation.